Patient-Provider Interactions Affect Symptoms in Gastroesophageal Reflux Disease: A Pilot Randomized, Double-Blind, Placebo-Controlled Trial. - Michelle L Dossett; Lin Mu; Roger B Davis; Iris R Bell; Anthony J Lembo; Ted J Kaptchuk; Gloria Y Yeh (PLoS ONE)
Background It is unclear whether the benefits that some patients derive from complementary and integrative medicine (CIM) are related to the therapies recommended or to the consultation process as some CIM provider visits are more involved than conventional medical visits. Many patients with gastrointestinal conditions seek out CIM therapies, and prior work has demonstrated that the quality of the patient-provider interaction can improve health outcomes in irritable bowel syndrome, however, the impact of this interaction on gastroesophageal reflux disease (GERD) is unknown. We aimed to assess the safety and feasibility of conducting a 2 x 2 factorial design study preliminarily exploring the impact of the patient-provider interaction, and the effect of an over-the-counter homeopathic product, Acidil, on symptoms and health-related quality of life in subjects with GERD. Methods 24 subjects with GERD-related symptoms were randomized in a 2 x 2 factorial design to receive 1) either a standard visit based on an empathic conventional primary care evaluation or an expanded visit with questions modeled after a CIM consultation and 2) either Acidil or placebo for two weeks. Subjects completed a daily GERD symptom diary and additional measures of symptom severity and health-related quality of life. Results There was no significant difference in GERD symptom severity between the Acidil and placebo groups from baseline to follow-up (p = 0.41), however, subjects who received the expanded visit were significantly more likely to report a 50% or greater improvement in symptom severity compared to subjects who received the standard visit (p = 0.01). Total consultation length, perceived empathy, and baseline beliefs in CIM were not associated with treatment outcomes. Conclusion An expanded patient-provider visit resulted in greater GERD symptom improvement than a standard empathic medical visit. CIM consultations may have enhanced placebo effects, and further studies to assess the active components of this visit-based intervention are warranted. Trial registration ClinicalTrials.gov NCT01915173.